2013
DOI: 10.1097/mej.0b013e32835e078e
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of highly frequent users of a Swiss academic emergency department

Abstract: Highly frequent users of a Swiss academic ED are a highly vulnerable population. They are in poor health and accumulate several risk factors of being even in poorer health. The small number of patients and their high level of insurance coverage make it particularly feasible to design a specific intervention to approach their needs, in close collaboration with their primary care practitioner. Elaboration of the intervention should focus on social reinsertion and risk-reduction strategies with regard to substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
6
24
0
2
Order By: Relevance
“…A combination of social and medical factors was markedly associated with frequent ED use, as FUs were 10 times more likely to have three of them (of a total of eight factors; 95% CI = 5.1 to 19.6). This result is confirmed by Althaus et al [56] in a retrospective chart review on hyperfrequent users (12 attendances or more during a year): they were 13 times more likely than non-FUs (65.5 vs 5.0%) to present three or more of the risk factors of vulnerability that Bieler et al referred to [46] and 2.2 times more likely than FUs (62.5 vs 28.4%). Finally, unpublished, local, prospective, cross-sectional data (Bodenmann P. et al, in progress) obtained between November 2009 and June 2010 has demonstrated differences between 226 FUs and 173 infrequent users.…”
Section: Discussionsupporting
confidence: 59%
“…A combination of social and medical factors was markedly associated with frequent ED use, as FUs were 10 times more likely to have three of them (of a total of eight factors; 95% CI = 5.1 to 19.6). This result is confirmed by Althaus et al [56] in a retrospective chart review on hyperfrequent users (12 attendances or more during a year): they were 13 times more likely than non-FUs (65.5 vs 5.0%) to present three or more of the risk factors of vulnerability that Bieler et al referred to [46] and 2.2 times more likely than FUs (62.5 vs 28.4%). Finally, unpublished, local, prospective, cross-sectional data (Bodenmann P. et al, in progress) obtained between November 2009 and June 2010 has demonstrated differences between 226 FUs and 173 infrequent users.…”
Section: Discussionsupporting
confidence: 59%
“…They also frequently reported social isolation and histories of trauma. Trauma exposure and social isolation have both been associated with greater healthcare utilization and costs [4, 1923]. Frequent ED users in this sample often connected their health concerns to past traumatic events, a finding that has been noted in other qualitative samples of frequent ED users [24].…”
Section: Discussionmentioning
confidence: 66%
“…However, in order to maximize the generalizability of our findings, we recruited a representative study sample of frequent ED users. 16,45 In addition, the design of the Swiss health system-privatized but with universal coverage-allows for generalization of our findings to North America, Europe and parts of Asia. Second, the enrollment rate of 47.5 % could have biased or contributed to our non-significant results.…”
Section: Discussionmentioning
confidence: 85%